Strategi Pengembangan Pariwisata di Kabupaten Grobogan - Zulfa Illiyyiin; Herbasuki Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
The tourism development has grand purpose to increase the number of tourist visits so that increase the local revenues. Moreover, in the tourismdevelopment is related to the infrastructure that need government support, the provision of information about travel and the tourism products and services marketing. The tourismdevelopment sector as one of the efforts in the pursuit of increase economic growth has been planned by the GroboganGovernment. This study used the theories on the development strategy in strategy planning, tourism, SWOT analysis and Litmus Test. The study methodis descriptive qualitative by data collecting technique through interviews, observation and documentation. The informants in this study are the employees of Department for Youth, Sport, Culture and Tourism Affairs in Grobogan.The writer also gain the data from visitors and the public travel in Grobogan area. The tourism development in Grobogan need improvement in infrastructure and lack of budgetary funds that require investors to cooperate. Toreach appropriate strategies in this study, the writer used SWOT analysis. The strategy analyze the internal factors and external factors to determine Strength, Weakness, Opportunity and Threat. Furthermore, to measure the level of appropriate strategies, the data tested with Litmus Test. In this test, the writer get the priority scale strategy on the tourismdevelopment is SO strategy. Both Strength and Opportunity gave the possibility ofthe organizations to evolve quickly by using Strength from the internal environment to take opportunities from the external environment of the organization.